Analysis of sakka customary law' display to the community ada' Tuho in sambabo village ulumanda district Majene regency - Sulaeman Sulaeman; Fadli Yasser Arafat Juanda (Indonesia Prime, 2021)
Marriage is a social bond or legal bond between persons that forms kinship. Marriage generally begins and is officiated with a ceremony with a wedding ceremony. Generally, marriages are performed with the intention of making a family. The family is the smallest unit of society consisting of the head of the family and several people who are gathered and live somewhere and interdependently. Customary law that regulates forms of marriage, ways of application, marriage ceremonies, ways of marriage and the termination of marriage in Indonesia. The rule of marriage law in each region is different, due to their different societal, customs, religions and beliefs